Children in marketing: A review, synthesis and research agenda - Sigirci, Ozge; Gegez, A. Ercan; Aytimur, Hilal; Gegez, E. Eser (Wiley, 2022)
Children have received much research attention in many different academic disciplines within social sciences, including marketing. The main objective of this study is to provide a comprehensive overview of the marketing literature to investigate the historical evolution of the studies on children and shed light on possible gaps which could serve as new research areas for future studies. To the authors' best knowledge, there have been a few attempts on the topic, mostly with a narrow focus on only some aspects of this important concept. The significance of this current research is that it reviews 423 articles from marketing-related journals and evaluates the development of thought on children from every marketing-based perspective that once has been a subject of scholarly attention. In this study, we examined leading articles, authors and institutions, methodologies used, countries data collected from, and the age of the sample. In addition, an auto-correlation map is created to identify all the research domains in marketing literature related to children. Our correlation matrix indicates that major subareas in children and marketing literature are children's consumer socialization and role in family decision-making, materialism, vulnerability and ethics, food, brands, and advertising. Findings revealed that while marketing scholars have shown great attention to children during the last two decades and a wide array of articles have been frequently published on the eight sub-areas mentioned, marketing literature is still underdeveloped on three aspects: sustainability, technology and digitalization, and cross-cultural differences.
Keywords: Advertising; Brand; Children; Consumer Socialization; Food; Marketing; Systematic Review; Family Communication Patterns; Fast-Food Consumption; Consumer Socialization; Decision-Making; Self-Esteem; Advertising Literacy; Persuasion Knowledge; Childhood Obesity; Brand-Placement; Parental Style